2016
DOI: 10.5539/gjhs.v8n9p302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dietary Intake between Polycystic Ovary Syndrome Women and Controls

Abstract: Polycystic Ovary syndrome (PCOS) is a complicated endocrinopathy affecting women in reproductive age. The crucial role of obesity and insulin resistance in progression of metabolic and cardiovascular features of PCOS has been confirmed. Although it has been suggested that there is a possible association between dietary pattern and risk of PCOS, few studies investigating the diet composition of PCOS women. The aim of this study was to compare the dietary intakes between women with polycystic ovary syndrome (PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
5
23
0
11
Order By: Relevance
“…However, the body mass index was a confounding factor for these results. Further, previous studies found a high dietary glycemic index and glycemic load and a low fiber intake among patients with PCOS …”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, the body mass index was a confounding factor for these results. Further, previous studies found a high dietary glycemic index and glycemic load and a low fiber intake among patients with PCOS …”
Section: Discussionmentioning
confidence: 85%
“…No difference was found in total energy intake and intake of nutrient elements in the present study. Likewise, most other studies did not find significant differences in protein, fat, and carbohydrate intake between women with PCOS and the control group . Wild et al .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Women with PCOS have been reported to consume greater glycemic loads than women without PCOS (Douglas et al, ; Shishehgar et al, ). However, we found higher glycemic loads in PCOS only in those with IR (Table ) similar to findings reported by Graff et al ().…”
Section: Discussionmentioning
confidence: 99%